Zoning of Trowulan Cultural Heritage Area as an Effort to Regulate the Function of Space in Cultural Paradigm - Fatihah, Lauhil; Riyanto, Edi Dwi; Arifin, Muhammad Thohir (Titian: Jurnal Ilmu Humaniora, 2024)
Zoning of Cultural Heritage is one of the government's efforts to protect Cultural Heritage from various factors that can threaten the existence of Cultural Heritage in the current era of modernization. One of the Cultural Heritage zonings implemented by the government is the Trowulan National Cultural Heritage Area Zoning. The zoning is implemented to regulate the function of space by considering the preservation of Cultural Heritage as a fundamental aspect in the Trowulan National Cultural Heritage Area. This research aims to find out how the zoning of Cultural Heritage is implemented in the Trowulan National Cultural Heritage Area to regulate the function of space through the cultural paradigm. This research uses qualitative research methods with a case study approach, namely the Trowulan National Cultural Heritage Area. The techniques used to collect data in this research are observation, interviews, and documents. The analysis method used in this research is interpretative qualitative method. The results of this research show that through the cultural paradigm, the zoning of the Trowulan National Cultural Heritage Area really needs to be done to provide regulations that regulate the function of space to maintain the existence of Cultural Heritage so that it can be passed down to the next generation of the Indonesian Nation.